On Some Interesting Problems of Control Systems - Laszlo Keviczky; Csilla Bányász (Association for Scientific Computing Electronics and Engineering (ASCEE), 2022)
The paper discusses some interesting mainly philosophical paradigms of the modelling and control areas, which are still partly unsolved and/or only partially studied.